2021
DOI: 10.1007/s11270-021-05303-z
|View full text |Cite
|
Sign up to set email alerts
|

High Mercury Concentrations of European Perch (Perca fluviatilis) in Boreal Headwater Lakes with Variable History of Acidification and Recovery

Abstract: High dissolved organic carbon and low pH are often associated with elevated mercury content of fish in boreal lakes, but less is known about the fish mercury dynamics in lakes recovering from acidification stress. We measured total mercury concentration (THg) in muscle of European perch (Perca fluviatilis) and evaluated the overall correlation with environmental and growth variables in 24 boreal headwater lakes in the 2010s. We found negative correlations of length-corrected perch THg with lake pH and perch gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…Furthermore, low pH in catchment and lake could enhance mercury methylation and increase THg content in fish (Compeau and Bartha, 1984;Gilmour and Henry, 1991;Wyn et al, 2009;Rask et al, 2021). Many studies show dilution of mercury due to high growth rate (Simoneau et al, 2005;Karimi et al, 2007;Rask et al, 2021;Moslemi-Aqdam et al, 2022), but in this study pike growth rate showed a positive relationship with THg content in the model. Positive relationship between total mercury and growth rate could be related on faster growing individuals feeding on higher trophic level.…”
Section: P3: Explanatory Models Of Thg In Pikementioning
confidence: 50%
See 1 more Smart Citation
“…Furthermore, low pH in catchment and lake could enhance mercury methylation and increase THg content in fish (Compeau and Bartha, 1984;Gilmour and Henry, 1991;Wyn et al, 2009;Rask et al, 2021). Many studies show dilution of mercury due to high growth rate (Simoneau et al, 2005;Karimi et al, 2007;Rask et al, 2021;Moslemi-Aqdam et al, 2022), but in this study pike growth rate showed a positive relationship with THg content in the model. Positive relationship between total mercury and growth rate could be related on faster growing individuals feeding on higher trophic level.…”
Section: P3: Explanatory Models Of Thg In Pikementioning
confidence: 50%
“…Increased catchment properties could enhance higher THg content in pike, however, nutrient enrichment from larger catchment area could have an inhibiting effect through biodilution of THg in lake biomass (Todorova et al, 2015). Furthermore, low pH in catchment and lake could enhance mercury methylation and increase THg content in fish (Compeau and Bartha, 1984;Gilmour and Henry, 1991;Wyn et al, 2009;Rask et al, 2021). Many studies show dilution of mercury due to high growth rate (Simoneau et al, 2005;Karimi et al, 2007;Rask et al, 2021;Moslemi-Aqdam et al, 2022), but in this study pike growth rate showed a positive relationship with THg content in the model.…”
Section: P3: Explanatory Models Of Thg In Pikementioning
confidence: 58%
“…Perch had high THg concentrations too, which was somewhat surprising considering that their δ 15 N isotope signatures positioned them at a trophic level that was lower than the other piscivores and similar to large sparsely rakered whitefish. A plausible reason for this comparative difference is the slow somatic growth rate and high longevity of perch in the Pasvik watercourse, which may have resulted in inverse growth dilution of Hg, as has been reported for other European perch populations (Rask et al, 2021).…”
Section: Discussionmentioning
confidence: 80%